Decoding the anomalies: a genome-based analysis of Bacillus cereus group strains closely related to Bacillus anthracis - Magome, Thuto Gomolemo; Surleac, Marius; Hassim, Ayesha; Bezuidenhout, Cornelius Carlos; van Heerden, Henriette; Lekota, Kgaugelo Edward (Frontiers in Microbiology, 2025)
IntroductionThe Bacillus cereus group encompasses a complex group of closely related pathogenic and non-pathogenic bacterial species. Key members include B. anthracis, B. cereus, and B. thuringiensis organisms that, despite genetic proximity, diverge significantly in morphology and pathogenic potential. Taxonomic challenges persist due to inconsistent classification methods, particularly for B. cereus isolates that resemble B. anthracis in genetic clustering.MethodsThis study investigated B. cereus group isolates from blood smears of animal carcasses in Kruger National Park, uncovering an unusual isolate with B. cereus features based on classical microbiological tests yet B. anthracis-like genomic similarities with an Average Nucleotide Identity (ANI) of ≥95%. Using comparative genomics, pan-genomics and whole genome Single Nucleotide Polymorphism (wgSNP) analysis, a total of 103 B. cereus group genomes were analyzed, including nine newly sequenced isolates from South Africa and a collection of isolates that showed some classification discrepancies, thus classified as “anomalous.”Results and discussionOf the 36 strains identified as B. anthracis in GenBank, 26 clustered phylogenetically with the four confirmed B. anthracis isolates from South Africa and shared 99% ANI. Isolates with less than 99% ANI alignment to B. anthracis exhibited characteristics consistent with B. cereus and/or B. thuringiensis, possessing diverse genetic profiles, insertion elements, resistance genes, and virulence genes features, contrasting with the genetic uniformity of typical B. anthracis. The findings underscore a recurrent acquisition of mobile genetic elements within B. cereus and B. thuringiensis, a process infrequent in B. anthracis.ConclusionThis study highlights the pressing need for standardized taxonomic criteria in B. cereus group classification, especially as anomalous isolates emerge. This study supports the existing nomenclature framework which offers an effective solution for classifying species into genomospecies groups. We recommend isolates with ANI ≥99% to standard reference B. anthracis be designated as typical B. anthracis in GenBank to maintain taxonomic clarity and precision.